ANALISIS PENGARUH CORPORATE GOVERNANCE DAN RESIKO TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR PERBANKAN DI BEI - Karpriana, Angga Permadi; Maulana, Arief Rio (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2018)
This study aims to determine the effect of corporate governance and risk to thefinancial performance of the banking sector companies listed on the Indonesian Stock Exchange (IDX). Variables tested for corporate governance is the Board ofCommissioners and Board of Directors. The risk represented by the variable Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR), while for the company's financial performance, this study uses the Return On Asset (ROA). This study using multiple regression analysis (multiple regression) as the independent variable is used more than one. Selection of the sample using purposive sampling method produced 24 banking companies. Variable Board of Commissioners (DKOM) has tcount 0.885 and sig of 0.403. Sig 0.403> Î± (0.05). Board of Directors (DDIR) has tcount 0.875 and sig of 0.392. Sig value 0,392> Î± (0.05). Capital Adequacy Ratio (CAR) has tcount of 0,361 and sig of 0.722. Sig 0.722> Î± (0.05). Loan Deposit Ratio (LDR) has tcount at 0.226 and sig of 0.824. Sig 0.824> Î± (0.05). The test results show that the Board of Commissioners, Board of Directors, the Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio(LDR), no effect on the financial performance of the banking sector.Keywords: Corporate Governanvce, Dewan Komisaris, Dewan Direksi, CapitalAdequacy Ratio, Loan Deposit Ratio, Return On Asset.